A study to compare the effects of platelet rich plasma and cryotherapy on cervical erosion - Verma, Punam Amarjit; Makhija, Nishi; Jain, Reema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This research work aimed to study the effects of platelet rich plasma (PRP) application on cervical erosion and to compare its efficacy with cryotherapy as alternate mode of therapy. Methods: 100 sexually active women more then 20 yrs of age with symptomatic cervical erosion were included in the study. 50 were treated with PRP and remaining 50 were treated with cryotherapy. PRP was prepared from patients own blood, no anaesthesia was used. Patients were followed at 2 weeks, 4 weeks and 12 weeks. Results: At 2 weeks follow up significant relief was obtained in PRP group (82%) while patients who underwent cryotherapy had a lot of white discharge (only 4% were relieved). At 4 weeks and 12 weeks the difference in symptomatic relief was almost similar in both groups. Conclusions: PRP is a safe, effective, easy to obtain, economical and a promising modality in the treatment of cervical erosion. Relief obtained after single application of PRP was extremely remarkable at 2 weeks.